Unfavorable body composition and quality of life among community-dwelling middle-aged and older adults: What really matters?. (October 2020) - Hwang, An-Chun; Lee, Wei-Ju; Peng, Li-Ning; Liu, Li-Kuo; Lin, Ming-Hsien; Loh, Ching-Hui; Chen, Liang-Kung
Highlights: Obese community-living people had significantly lower PCS scores. The effect was enhanced when low muscle or bone mass were present. Z-transformed central obesity was positively associated with MCS. Abstract: Objective: To evaluate the impact of individual components of unfavorable body composition and their combinations on quality of life (QoL) among middle-aged and older adults. Methods: Data from 1779 participants (53.1 % female; mean age 63.9 ± 9.2 years) from the I-Lan Longitudinal Aging Study were analyzed in this study. Demographic characteristics of all participants and data from anthropometric measurements, functional assessments, dual-energy X-ray absorptiometry scans, and surveys of QoL were obtained. Low skeletal muscle mass was defined by the Asian Working Group of Sarcopenia consensus, and obesity was defined by waist circumference (WC), body fat percentage, or body mass index (BMI). QoL was assessed by the 12-Item Short Form Health Survey version 2, which was divided into the physical component summary (PCS) and mental component summary (MCS). The composite score was determined based on the items of unfavorable body composition. Independent associations between unfavorable body composition components and QoL were evaluated by the multivariate linear regression model. Z transformation was performed to facilitate evaluation between different components of body composition and their relationship with QoL. Results: All definitions of obesity were significantly associated with a lower PCS score (WC: β=-1.2, SE = 0.3, p < 0.001; body fat percentage: β=-1.0, SE = 0.3, p < 0.001; BMI: β=-0.9, SE = 0.3, p = 0.002 in the fully adjusted model). The PCS score decreased linearly as the composite score of unfavorable body composition increased, especially when obesity was defined by WC (score = 1: β=-0.7, SE = 0.4, p = 0.053, score = 2: β=-1.1, SE = 0.4, p = 0.008; score = 3: β=-2.4, SE = 1.0, p = 0.013). After Z transformation, obesity was significantly negatively associated with the PCS score (β=-0.9∼-0.2, SE = 0.1∼0.2, p values all less than 0.01). In contrast, a one-standard-deviation increase in WC was associated with a significantly higher MCS score (β = 0.3, SE = 0.1, p = 0.019). Conclusions: Community-dwelling middle-aged and older people with obesity had significantly lower PCS scores, and the effect was enhanced when low skeletal muscle mass or osteopenia/osteoporosis was present. Central obesity was the only unfavorable body composition parameter with negative effects on both the physical and the mental domains of QoL. Further longitudinal or intervention studies are needed to evaluate the impact on QoL of changes in body composition that occur with aging.